IMPLEMENTASI MEDIA FLIP CARD DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Nazarni Khalisa, Najmi; Nanda Humaira, Nazwa; Amalinda, Sry; Ferdiyansyah, Aldy; Prihandoko, Yogi; Refia Rafianti, Wahdah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of attractive and interactive learning media is an important effort in supporting Social Studies learning in elementary schools. Based on this need, Flip Card learning media was developed to help students understand the topic of Indonesian cultural diversity in a more enjoyable and meaningful way. This media was designed with appealing visuals and concise materials that focus directly on the main concepts, aiming to improve students’ interest, motivation, and active participation during the learning process. This study employed a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. The results showed that the use of Flip Card media was able to create a more interactive learning atmosphere, increase students’ engagement during classroom activities, and broaden students’ understanding of cultural diversity in Indonesia. Although several technical limitations were identified, such as the limited number of cards and the need for initial adaptation in using the media, Flip Card still provided a positive contribution to the quality of Social Studies learning. Therefore, Flip Card learning media is considered suitable as an innovative learning medium for elementary school students.